2005
DOI: 10.1080/10473289.2005.10464701
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Fine Particles in Diesel Emissions Using a Real-Time Aerosol Monitor

Abstract: A real-time monitoring methodology to determine diesel fine particles in diesel emissions has been evaluated. The range of particle size captured by the monitor was ϳ0.1 m to 1 m. DustTrak real-time monitors were connected to the dilution tunnel of the vehicle exhaust to measure the emissions during the vehicle tests under both dynamic and steady-state driving conditions, and concentration data were recorded every 5 sec. Test variation of the real-time monitoring among different test days was similar to that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The total experimental setup can be found in [21]. [26]. A single stage partial flow dilution system (PFDS) was used in this study to dilute the representative exhaust gas sample drawn from the engine for PM measurements.…”
Section: Experimental Setup and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The total experimental setup can be found in [21]. [26]. A single stage partial flow dilution system (PFDS) was used in this study to dilute the representative exhaust gas sample drawn from the engine for PM measurements.…”
Section: Experimental Setup and Methodologymentioning
confidence: 99%
“…That exhaust is of concern because of its impact on visibility and for its potential health hazards. Particulate emissions can be classified as potential occupational carcinogen and can have a number of other negative health impacts associated with exposure [3][4][5][6]. It is generally agreed that diesel engines used in transport systems represent an important source of ambient particulate matter [7].…”
Section: Introductionmentioning
confidence: 99%
“…This sequential online nature makes it suitable for modeling the dynamics of human learning in our experiments. Similar process models have previously been applied to animal (Daw and Courville, 2008; Gershman et al, 2010) and human (Brown and Steyvers, 2009; Frank et al, 2010; Sanborn et al, 2010) learning, although the generative assumptions of those models differ from our own 4

The particle filtering algorithm maintains a set of L samples z (1: L ) t − 1 distributed approximately according to the posterior, P ( z t − 1 | c 1: t − 1 , x 1: t − 1 ).

…”
Section: Particle Filtering Algorithmmentioning
confidence: 96%
“…Gehrig et al (2007) examined the influence on PM 10 concentrations from dust associated with electric trains in Switzerland. A number of previous studies have reported EFs for on-road diesel trucks and buses (Jamriska et al, 2004;Zhu et al, 2005;Cheng et al, 2006;Park et al, 2011;Dallmann et al, 2012), but to our knowledge, similar studies have not been reported for diesel rail.…”
Section: Introductionmentioning
confidence: 47%
“…Instead, accurate measurements using the DustTrak require a comparison against a mass-based measurement for the aerosol of interest (Moosmuller et al, 2001). A number of previous EF studies have also used the DustTrak to rapidly measure several size fractions of PM and calculate EFs from individual vehicles (e.g., Park et al, 2011;Dallmann et al, 2012), but usually after calibration of the response factor against a massbased method (Jamriska et al, 2004;Zhu et al, 2005;Cheng et al, 2006). For our study, we calibrated the DustTrak against a mass-based TEOM measurement (described above).…”
Section: Methodsmentioning
confidence: 99%